2018
DOI: 10.1093/molbev/msy144
|View full text |Cite
|
Sign up to set email alerts
|

Exon-Capture-Based Phylogeny and Diversification of the Venomous Gastropods (Neogastropoda, Conoidea)

Abstract: Transcriptome-based exon capture methods provide an approach to recover several hundred markers from genomic DNA, allowing for robust phylogenetic estimation at deep timescales. We applied this method to a highly diverse group of venomous marine snails, Conoidea, for which published phylogenetic trees remain mostly unresolved for the deeper nodes. We targeted 850 protein coding genes (678,322 bp) in ca. 120 samples, spanning all (except one) known families of Conoidea and a broad selection of non-Conoidea neog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 91 publications
3
62
0
Order By: Relevance
“…This makes the technique a good candidate to be applied for Southern Ocean benthos studies where the limitation of well-preserved material is obvious. First studies have shown that the technique can offer new insights into the phylogeny and diversification of non-target species (e.g., Abdelkrim et al 2018;O'Hara et al 2019). Also population genetic patterns within lineages can be assessed especially when including co-enriched flanking regions of targeted genes (Dömel et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This makes the technique a good candidate to be applied for Southern Ocean benthos studies where the limitation of well-preserved material is obvious. First studies have shown that the technique can offer new insights into the phylogeny and diversification of non-target species (e.g., Abdelkrim et al 2018;O'Hara et al 2019). Also population genetic patterns within lineages can be assessed especially when including co-enriched flanking regions of targeted genes (Dömel et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Two venom-gland transcriptomes are published (Gonzales and Saloma 2014) that were not used primarily for phylogenetic purposes but for toxin research, because the Turridae are venomous and constitute a group of interest for bioactive compound discovery (Puillandre & Holford 2010). Finally, only one phylogenomic (RAD-seq) study (Abdelkrim et al 2018a) was published for species-delimitation purposes on eight species in the Xenuroturris/Iotyrris complex.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive efforts to understand the evolutionary relationships of the Conoidea, the most diverse superfamily of the Mollusca, have in recent years resulted in significant advances towards achieving a high-resolution, stable classification of the group. Where, until recently, very few family-level taxa comprised the entire superfamily, numerous studies have since refined the classification framework to now encompass 18 families (Bouchet et al 2011;Puillandre et al 2011;Abdelkrim et al 2018). While the taxonomic integrity of a few, most notably the Borsoniidae, appears fractious (Abdelkrim et al 2018), the majority are welldefined molecular lineages now subject to ongoing taxonomical scrutiny in light of this rapid nomenclatural proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Where, until recently, very few family-level taxa comprised the entire superfamily, numerous studies have since refined the classification framework to now encompass 18 families (Bouchet et al 2011;Puillandre et al 2011;Abdelkrim et al 2018). While the taxonomic integrity of a few, most notably the Borsoniidae, appears fractious (Abdelkrim et al 2018), the majority are welldefined molecular lineages now subject to ongoing taxonomical scrutiny in light of this rapid nomenclatural proliferation. One such family is the monotypic Bouchetispiridae, until recently only known from New Caledonia, and recognised as sister group to the conchologically very different Mitromorphidae (Kantor , Strong , et al 2012).…”
Section: Introductionmentioning
confidence: 99%